Da (des) esperança á esperança de inserção social da criança imigrante no novo lar : o papel da escola - Silva, Renata Santos da (2021)
Immigration in childhood is a more and more pertinent theme in the contemporary society and because of the increase of the migratory flow in the South American territory, countries like Brazil are becoming destinations of immigrant families from Latin America and the Caribbean. In this migratory flow, families and children arrive with the hope of having a best future with a more dignified life in their new home. This thesis has its origin in a research carried out in the city of Porto Alegre, capital of the state of Rio Grande do Sul, located in southern part of Brazil. The research has aimed to analyze how immigrant children from a school community experience the rights present in the Convention about the Rights of the Child while they are living in their new home. To achieve this goal, the methodological path was developed through a qualitative exploratory approach, where the Cartography was used as a procedure for collecting information. It was collected from April 2020 to January 2021.It was done through interviews with teachers, unsystematic observations and a questionnaire. Everything has been conducted according to the possibility of going to the field during the COVID-19 pandemic. The information was analyzed according to Content Analysis Categorical and following the presuppositions of Laurence Bardin. The categories that emerged from the field were called Hope (lessness), Situations of Deprivation of Rights Experienced by Immigrant Children in their New Home, and The Immigrant Child in their Routine of the School Life. These categories encompass the issues verified in the field and demonstrate that immigrant children experience, in the daily life of their new home, deprivation of the rights present in the Convention about the Rights of the Child. The first category points out that immigrant children do not find the necessary assistance for their full development in the government public policies. The second category, which deals with immigrant children in everyday school life, demonstrates that the inexistence of guiding and standardizing policies in the institution that maintains the education system, turn very difficult the access to it of immigrant students and can generate misunderstandings in the pedagogical management. It was possible to conclude that, at school, situations of racism and xenophobia are added to the social invisibility of the immigrant child, demonstrating the inefficiency of the educational policies that propose the right to education for all.